Lao She's Teahouse and its two English translations : exploring Chinese drama translation with systemic functional linguistics /: exploring Chinese drama translation with systemic functional linguistics. (2020) - (Professor of translation studies), Wang, Bo; Ma, Yuanyi
No abstract available